Mild diabetes models and their maternal-fetal repercussions - Damasceno, Débora Cristina [UNESP]; Sinzato, Y. K. [UNESP]; Bueno, A. [UNESP]; Netto, A. O. [UNESP]; Dallaqua, B. [UNESP]; Gallego, F. Q. [UNESP]; Iessi, I. L. [UNESP]; Corvino, S. B. [UNESP]; Serrano, R. G. [UNESP]; Marini, G. [UNESP]; Piculo, F. [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; et al. (Hindawi, 2013)
The presence of diabetes in pregnancy leads to hormonal and metabolic changes making inappropriate intrauterine environment, favoring the onset of maternal and fetal complications. Human studies that explore mechanisms responsible for changes caused by diabetes are limited not only for ethical reasons but also by the many uncontrollable variables. Thus, there is a need to develop appropriate experimental models. The diabetes induced in laboratory animals can be performed by different methods depending on dose, route of administration, and the strain and age of animal used. Many of these studies are carried out in neonatal period or during pregnancy, but the results presented are controversial. So this paper, addresses the review about the different models of mild diabetes induction using streptozotocin in pregnant rats and their repercussions on the maternal and fetal organisms to propose an adequate model for each approached issue. © 2013 D. C. Damasceno et al.
Keywords: streptozocin; diabetes mellitus; diabetogenesis; disease model; embryo development; experimental animal; experimental model; human; hyperglycemia; maternal welfare; mother fetus relationship; nonhuman; oxidative stress; pancreas islet; pregnancy; priority journal; review; uterus